PENGARUH MEDIA GAMBAR BERSERI PENDEKATAN TASK ANALYISIS TERHADAP KETERAMPILAN MENCUCI TANGAN PESERTA DIDIK HAMBATAN INTELEKTUAL SEDANG - Alghifari Saputra, Mirza; Yulian Agus Suminar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Handwashing skills are an important aspect of self-care; however, these skills have not been optimally developed among students with moderate intellectual disabilities. This study aimed to determine the effect of using serial picture media with a task analysis approach on the handwashing skills of students with moderate intellectual disabilities at SLB Negeri 2 Yogyakarta. This study employed a quantitative approach with a pre-experimental one-group pre-test post-test design. The subjects consisted of six students with moderate intellectual disabilities selected using a total sampling technique. Data were collected through a performance test using an observation sheet instrument consisting of ten indicators of handwashing skills. The data were analyzed using the nonparametric Wilcoxon Signed Rank Test using SPSS version 25. The results showed an increase in the mean score of handwashing skills from 15.17 in the pre-test to 25.50 in the post-test. The Wilcoxon test results indicated a significance value of 0.027 (p < 0.05). Based on these findings, it can be concluded that the use of serial picture media with a task analysis approach has a significant effect on improving the handwashing skills of students with moderate intellectual disabilities at SLB Negeri 2 Yogyakarta